Local Economic Empowerment: A Strategy to Reduce Economic Inequality in Regions - harsono, Iwan; Pasalbessy, Victor F; Latuheru, Anita (MSJ : Majority Science Journal, 2025)
This study aims to analyze local economic empowerment strategies as an effort to reduce this gap. The method used is the Systematic Literature Review (SLR) with a study of related literature over the past five years. The results of the study indicate that strengthening Micro, Small, and Medium Enterprises (MSMEs), developing a creative economy based on local potential, and empowering farmer groups, fishermen, and cooperatives are effective strategies in increasing community productivity and income. Multi-party synergy involving local governments, communities, NGOs, the private sector, and academics, together with inclusive policies, training, access to financing, and infrastructure development, are the keys to successful empowerment. However, there are still obstacles such as limited access to capital, low digital literacy, and infrastructure inequality that need to be addressed. This study recommends strengthening sustainable policies, increasing human resource capacity, expanding access to financing, and developing strategic partnerships to support local economic empowerment. Thus, local economic empowerment can be an effective solution in reducing economic inequality and encouraging equitable and inclusive regional development